Dual diagnosis the evolving conceptual framework - Stohler, Rudolf; Rössler, Wulf 1947- (Karger, 2005)
Co-morbidity of substance abuse and mental illness is among the most prevalent mental disorders worldwide and places an enormous burden on individuals and society. This book begins with a historical overview of the conceptual issues behind dual diagnosis and presents recent developments in conceptualization and treatment. Several reviews evaluate the latest etiological theories on the association of mental illness with substance use disorders. One chapter deals with genetic and behavioral aspects by looking at twin studies. The link between alcohol use and mental disorders, the role of a pre-existing attention deficit hyperactivity disorder on the development of substance use disorders, the contribution of substance abuse to neurocognitive impairments as well as various assessment options are also discussed. Finally, the model of the ‘modified therapeutic communities’ as an emerging modality for the provision of integrated treatment is presented.This topical and outstanding collection of articles provides an excellent overview over the stimulating scientific research that is currently taking place in the field of dual diagnosis
Keywords: Psychiatry; Psychology; Addiction; Genetics; Neurobiology; Drogenmissbrauch; Sekundärkrankheit; Psychische Störung; Aufsatzsammlung